Sistem Informasi Rekomendasi Penentuan Jurusan Sekolah Menengah Atas dengan Metode K-Means Clustering dan Algoritma Topsis Berbasis Multi User - Syam Gunawan; Hanif Jusuf (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
Choosing a major for students is a positive step taken to focus students according to their potential, this is considered important as a department, students are expected to be able to develop academic abilities according to their field of expertise. In previous studies, majors in SMA are currently still done manually and have a tendency to look at students' academic scores only. If the student's score meets the KKM standard (Minimum Completeness Criteria) set by the school, it can be determined that the student will enter one of the existing majors. Meanwhile, to see student interest, students are usually asked to fill out a questionnaire manually. The manual method is less practical and takes a long time, prone to errors in examination and assessment so that errors can occur in determining the value. Mistakes in choosing a major will be detrimental to students, both in terms of cost and time. The decision support system for selecting majors in high school uses the K-Means Clustering and the Algoritma Topsis was built to help schools make it easier to determine major recommendations. The criteria used are students' academic scores and student interests.